Effects of enhanced fermentation with high-yielding strains of Tetramethylpyrazine on flavor quality of Douchiba - Panpan Yang; Qin Wang; Yurou Yang; Anyan Wen; Haiying Zeng; Na Liu; Likang Qin (Food Chemistry: X)
Douchiba (DCB) is a nutritious food rich in various functional components such as Tetramethylpyrazine (TTMP), and the strain fermentation is crucial for enhancing its quality. This work utilized Bacillus subtilis S2–2 and Hyphopichia burtonii S6-J1 with high TTMP production for fermentation of soybeans to optimize the pre-fermentation process and to evaluate the flavor quality of mature DCB. The concentration of TTMP in DCB fermented by mixed microbial (MG) was 2.95 times higher than that of of the control. Furthermore, the concentrations of taste substances, organic acids, free amino acids, and free fatty acids in MG were significantly increased. 87 flavor compounds were detected by gas chromatography-ion mobility spectrometry. The content of aldehydes, alcohols, esters, acids, and pyrazines flavor compounds was higher in MG, with esters and alcohols being notably higher than in other groups. Additionally, the highest comprehensive score of flavor quality was obtained in MG by principal component analysis.